2020
DOI: 10.1098/rspb.2019.2834
|View full text |Cite
|
Sign up to set email alerts
|

Into the wild: microbiome transplant studies need broader ecological reality

Abstract: Gut microbial communities (microbiomes) profoundly shape the ecology and evolution of multicellular life. Interactions between host and microbiome appear to be reciprocal, and ecological theory is now being applied to better understand how hosts and their microbiome influence each other. However, some ecological processes that underlie reciprocal host–microbiome interactions may be obscured by the current convention of highly controlled transplantation experiments. Although these approaches have yielded invalu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 90 publications
3
35
0
Order By: Relevance
“…Here we ruled out stress as a determining factor as baseline and stressinduced corticosterone did not explain PSP. Further manipulative experiments, such as using a wide range of food rewards, or microbial transplantation experiments 12,61 in the absence of dietary differences would provide additional support that the microbiome itself caused the change in problem solving performance.…”
Section: Discussionmentioning
confidence: 99%
“…Here we ruled out stress as a determining factor as baseline and stressinduced corticosterone did not explain PSP. Further manipulative experiments, such as using a wide range of food rewards, or microbial transplantation experiments 12,61 in the absence of dietary differences would provide additional support that the microbiome itself caused the change in problem solving performance.…”
Section: Discussionmentioning
confidence: 99%
“…Microbiome transplant studies represent an important and increasingly applied approach to characterize host-microbiota interactions. While stating that although there is a clear need for highly controlled microbiome transplant experiments, Greyson-Gaito et al [8] reviewed the breadth of ecological reality in microbiome transplant studies and identified nine experimental conditions that affect EcoReality. Their analysis suggests that the 'EcoReality' of microbiota transplant studies has increased over time, and they present a roadmap for enhancing EcoReality in future transplantation experiments.…”
Section: Methodological and Analytical Approaches For Characterizing mentioning
confidence: 99%
“…However, manipulating host-microbiota interactions in animal hosts is arguably a more challenging endeavour. Greyson-Gaito et al [8] explore the power of microbiota transplants for testing the impact of gut microbiota on host health and phenotype, cautioning about the importance of considering the ecological realism of the transplant when interpreting the results.…”
Section: Effects Of the Microbiome On Phenotype Ecology And Evolutionmentioning
confidence: 99%
See 2 more Smart Citations